2013
DOI: 10.1002/cncr.28531
|View full text |Cite
|
Sign up to set email alerts
|

Genomics of racial and ethnic disparities in childhood acute lymphoblastic leukemia

Abstract: While the cure rates of childhood acute lymphoblastic leukemia (ALL) have improved dramatically in the past 40 years, not all children have benefited equally from this impressive progress. Racial and ethnic disparities in the incidence and treatment outcome of childhood ALL persist with Hispanic children having an elevated risk of developing ALL and one of the lowest survival rates after ALL therapy. A critical barrier to progress is that we lack the understanding of the causes of ALL disparities, particularly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
127
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(139 citation statements)
references
References 70 publications
7
127
1
4
Order By: Relevance
“…This study has identified some key areas of deviation from established guidelines and offers the opportunity to reflect and improve on our prescribing practices. subspecialty unit and ethnicity implies certain ethnic groups may be more prone to certain diseases; this is consistent with previous findings [28][29][30].…”
Section: Resultssupporting
confidence: 92%
“…This study has identified some key areas of deviation from established guidelines and offers the opportunity to reflect and improve on our prescribing practices. subspecialty unit and ethnicity implies certain ethnic groups may be more prone to certain diseases; this is consistent with previous findings [28][29][30].…”
Section: Resultssupporting
confidence: 92%
“…Previous studies have reported that the risk of hematological malignancies varies significantly among different ethnic groups (9,13,134,135). The present meta-analysis indicated that there was no association between CDKN2A methylation and the risk of leukemia (P=0.16) in Europeans, while a significant association was observed in Chinese populations (P<0.00001).…”
Section: Cases (N) Controls (N) -------------------------------------contrasting
confidence: 56%
“…These disparities are likely due to a combination of genetic, environmental and socioeconomic factors (13), which may affect epigenetic changes. Epigenetics, such as DNA methylation, have been shown to play an important role in cancer susceptibility (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…33,34 Together, these data provide a plausible explanation for increased incidence and poor outcomes of Hispanic patients with B-ALL and may explain the higher incidence of Ph-like ALL seen in adults within the United States vs other non-Hispanic Northern European populations. 35,36 The significantly high number of patients of Hispanic ethnicity in our study reflects the referral pattern for our institution.…”
Section: Discussionmentioning
confidence: 73%